Physical-chemical quality of 'Cabernet Sauvignon' clones in high altitude regions of Santa Catarina State, Brazil - Brighenti A.F.* (2012)
The clone refers to a vine cultivar that is selected for specific qualities, such as resistance to certain diseases or desired cluster size, taste or smell. Rootstocks are a link between the soil and the scion, they play an important role in vine adaptation to environmental factors. The objective of this study was to evaluate five 'Cabernet Sauvignon' clones grafted on two rootstocks and their influence on fruit quality. The experiment was conducted in Villa Francioni vineyards located at the city of São Joaquim (28°17'S; 49°56'W, altitude 1350 m), in Santa Catarina State, Brazil. The experimental design was randomized blocks, with three blocks and 20 plants per plot. The plants of 'Cabernet Sauvignon' were grafted on 1103 P and 3309 C and conducted in vertical shoot positioning trellis. The clonal selections evaluated were 169, 337, 170, 341, 339 and R5. The scion-rootstock combinations were 169 on 1103 P, 169 on 3309 C, 337 on 1103 P, 170 on 3309 C, 339 on 3309 C, 341 on 1103 P and R5 on 1103 P. The variables analysed were cluster and 50 berries weight, number of berries per cluster, berry diameter, cluster compactness, anthocyanins contents (mg L-1), total polyphenols, tannins, pH, total soluble solids, acidity (meq L-1) and color intensity. Data were submitted to analysis of variance and Tukey's test (5% probability). To the variables total soluble solids and acidity, the clone 169 on 1103 P presented the best results, while to pH the clone 170 on 3309 C was better. The maximum concentration of anthocyanins was observed in 339 grafted on 3309 C. The highest levels of total polyphenols, tannins and color intensity were observed in R5 on 3309 C.